(untitled) (Sociología y Tecnociencia, 2013)
Sex toys, and the vibrator as its greatest exponent in the passion party world, have become a totemic sex trend in Western sexual culture, going beyond their functional role for both men and women. In the neoliberal postcapitalist societies – based on compulsive, virtual and hedonist consumption – erotophilia is developed and expanded according to the existing sexual imaginary. An overview of the erotic gadgets and their heterosexual practice provide an interesting element to be analyzed to establish the validity of the sex androcentric model, which has been found poor in terms of female sexual satisfaction.